IMPLEMENTASI SISTEM PENGGAJIAN RESTORAN MENGGUNAKAN METODE BAGI HASIL BERBASIS WEB - Orlando, Rio; Bororing, Grace Martha Geertruida (Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The influence of technology has been very attached to life and everyday life in every way. The development of this technology has brought many changes to society. most people have switched from conventional systems to digital systems, even automation. Now all sales data, purchases, transactions, and other things in a business are very easy to manage and access. In the process of making this web-based payroll system, researchers are looking for, and studying theories related to websites and payroll systems. This research was conducted using the agile method. The design of the system made includes use cases, activity diagrams, class diagrams, interface designs, and implementation of the system whose purpose is to describe the workings of the payroll system. From the research conducted, it can be said that with this payroll system, it can make it easier to calculate the distribution of profits between owners, investors, and employees. In addition, financial administration has also become clearer and well-organized. In addition, employees feel benefited by this system so that employee performance can increase and restaurant income can increase rapidly. Keywords: Restaurant Payroll Application, Payroll System, Profit Sharing.